When do bystanders get help from teachers or friends? Age and group membership matter when indirectly challenging social exclusion - Yüksel, Ayşe Şule; Palmer, Sally B.; Argyri, Eirini Ketzitzidou; Rutland, Adam (Frontiers in Psychology, 2022)
We examined developmental changes in British children’s (8- to 10-year-olds) and adolescents’ (13- to 15-year-olds, N = 340; Female N = 171, 50.3%) indirect bystander reactions (i.e., judgments about whether to get help and from whom when witnessing social exclusion) and their social-moral reasoning regarding their reactions to social exclusion. We also explored, for the first time, how the group membership of the excluder and victim affect participants’ reactions. Participants read a hypothetical scenario in which they witnessed a peer being excluded from a school club by another peer. We manipulated the group membership of the victim (either British or an immigrant) and the group membership of the excluder (either British or an immigrant). Participants’ likelihood of indirect bystander reactions decreased from childhood into adolescence. Children were more likely to get help from a teacher or an adult than getting help from a friend, whereas adolescents were more likely to get help from a friend than getting help from a teacher or an adult. For both indirect bystander reactions, children justified their likelihood of responding by referring to their trust in their teachers and friends. Adolescents were more likely to refer to group loyalty and dynamics, and psychological reasons. The findings support and extend the Social Reasoning Developmental (SRD) approach by showing the importance of group processes with age in shaping children’s judgments about how to respond indirectly by asking for help from others, when they are bystanders in a situation that involves exclusion. The findings have practical implications for combating social exclusion and promoting prosocial bystander behavior in schools.